Efek Diuresis Ekstrak Seledri (Apium graviolens L.) pada Tikus Putih Jantan (Rattus norvegicus) - Annisa Marsha Evanti; Muchsin Doewes; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Celery (Apium graviolens L.) is known has some biochemical substances effect such as kalium nitrat, manitol, and apigenin/flavonoid which can result diuretic effect. This research aims at finding out the diuretic effect of celery extract (Apium graviolens L.) on the male white rats (Rattus norvegicus). Methods: The research is a laboratory experimental analytic study using the Randomized Controlled Trial design. The research subject is a number of 30 male white rats of Wistar Strain, 200 grams of body weight. They were divided into five treatment groups randomly. Group I was given 3 mL aquadest as negative control, group II was given 0,32 mg/3 mL hydrochlorotiazid as positive control, group III was given 1,2g/3 mL celery extract as dose I, group IV was given 2,4g/3 mL celery extract as dose II, and group V was given 4,8g/3 mL celery extract as dose III. Rats urine volume was measured every 4 hours for 16 hours. Results:The result of statistic calculation using ANOVA test with p = 0.000 (p < 0.001) shows that there are significant differences in total rats urine volume between group I, II, III, IV, and V in every observation time. The Post-hoc test shows significant differences between negative control and three dosages of celery extract (p < 0.05), and the similarities between positive control and three dosages of celery extract (p > 0.05). Conclusions: Through observing amount of urine volume and statistic calculation, it can be concluded that there is diuretic effect of celery extract on the male white rats. Celery extract at dose 2,4 g/3 mL has the highest diuretic effect but celery extract at 1,2 g/3 mL has the optimum diuretic effect. Keywords: Celery extract, diuretic effect, hydrochlorotiazid